The Influence of Personal Selling on Purchase Decisions of Ceuria Batik Garutan - Nurhalim, Elgy; Priansa, Donni Juni (Jurnal Wacana Ekonomi, 2023)
This research aims to determine the influence of Personal Selling on Purchasing Decisions, and explain the variables related to Personal Selling and Purchasing Decisions using quantitative research methods. Personal Selling is a direct communication activity between salespeople and potential consumers to introduce a product to potential consumers and make consumers understand the product so that they will try to validate it. Based on the results of research conducted by Batik Garutan, this personal mutual influence is needed by conducting surveys and observations in observing and collecting data directly at predetermined times where the sample has been determined. The data analysis method used is simple linear regression analysis. This research was conducted to test the extent of the influence of Personal Selling on purchasing decisions for Batik Ceuria. This research was conducted on Batik Ceuria consumers with a sample size of 100 respondents. This research obtained results where the influence of personal sales greatly influenced purchasing decisions for CeuRia Tulis Batik by increasing sales. Based on the results and discussion, it is explained that personal sales have a significant influence on purchasing decisions with a contribution of 61%, so that the personal sales variable is more influential than capital purchasing decisions, only having an influence of around 42%. on the calculation results of the coefficient of determination test.